Analysis of serum interleukin(IL)‐1α, IL‐1β and IL‐18 in patients with systemic sclerosis. Issue 4 (6th April 2019) - Lin, Emily; Vincent, Fabien B; Sahhar, Joanne; Ngian, Gene‐Siew; Kandane‐Rathnayake, Rangi; Mende, Rachel; Morand, Eric F; Lang, Tali; Harris, James
Abstract: Objectives: Systemic sclerosis (SSc) is an autoimmune disease characterised by fibrosis, vascular dysfunction and immune dysregulation. The pathogenesis of SSc remains poorly understood, although studies have indicated a role for the innate immune response. Methods: Here, we measured serum interleukin (IL)‐1α, IL‐1β and IL‐18 levels in 105 SSc patients and 47 healthy controls (HC) and analysed them with respect to multiple clinical parameters. Results: Serum IL‐18 concentrations were significantly higher in SSc patients than in HC, while no significant differences in concentrations of IL‐1α and IL‐1β were observed between SSc and HC. In both SSc and HC serum, IL‐1α and IL‐1β were positively correlated, while in SSc, both cytokines negatively correlated with IL‐18. Serum IL‐18 was significantly negatively correlated with both carbon monoxide transfer coefficient (KCO) and diffusing capacity of the lungs for carbon monoxide (DLCO). Serum IL‐1β was positively correlated with the modified Rodnan skin score (mRSS), particularly in patients with limited subtype. DLCO, KCO and tricuspid regurgitation (TR) velocity were significantly higher in patients with high serum IL‐1β. Serum IL‐1α was significantly lower in SSc patients with low KCO and positively correlated with KCO. SSc patients with high serum IL‐1α concentrations were more likely to have digital ulcers. Conclusions: Our data suggest that these IL‐1 family cytokines may have different roles in the pathogenesis of SSc fibrotic complications. Abstract : Serum levels of IL‐1α, IL‐1β and IL‐18 were measured in patients with systemic sclerosis (SSc) and analysed with respect to multiple clinical parameters. The data suggest potentially different roles for each cytokine in SSc.